Latihan Keterampilan Intelektual dan Kemampuan Pemecahan Masalah Secara Kreatif - Deetje Josephine Solang (Universitas Negeri Malang, 2016)
The study tries to investigate the utilization of intellectual creative skills within the framework of the triarchic theory of intelligence in reading activities. The subject in which the theory was applied was Bahasa Indonesia (Indonesian). This experimental study involved randomly selected seventh graders of Junior High School. There were three hypotheses to test in the study. First, the order of the three types of intellectual skills suggested in the triarchic theory of intelligence presented during training as well as during instruction has effects on students' performance in attempting creative solution to problems derived from reading texts in the subject of Bahasa Indonesia. Multiple comparisons were employed to test this hypothesis. Second, there is a significant difference in creative problem solving performances between the experimental and the control groups. Analysis of variance was carried out to test this hypothesis. Third, scholastic aptitude has a role in predicting the creative problem solving performance. ANACOVA was employed to test this hypothesis. The results show that the students show the best performance when they are trained using the thinking order of practice-synthesis-analysis.